Sistem Kendali Smart Aquarium Ikan Arwana Menggunakan Fuzzy Logic Controller (FLC) - Fitri Fitri; Mohammad Luqman; Chairunisa Chanza (Universitas Ngeri Malang, 2021)
Arowana fish require a pH level of 6.8 – 7.5 and a turbidity level of 7.5 NTU. The purpose of making this tool is to maintain the pH and turbidity of the arowana fish aquarium water. This tool uses a pH sensor E-201-C to measure water pH levels, a turbidity sensor SEN-0189 to detect water turbidity, and an ultrasonic sensor to measure water levels, using an ESP32 microcontroller. In controlling pH levels using the fuzzy logic controller method using set point 7. On pH levels to control pH levels using a mini up pump and mini down pump. If the pH less than 6.8 then the mini up pump will be active, and vice versa if the pH more than 7.5 then the mini down pump will be active. Meanwhile, to control the turbidity of the water, a DC 12V 1 pump is used for discharging dirty water and a DC 12V 2 pumps for filling clean water. The data read by the sensor can be monitored via the 128X64 OLED and the blynk application on the smartphone. That based on the test results on the control system for controlling pH levels of arowana fish aquarium water using the fuzzy method can work with an error value of less than 0.4. Meanwhile, controlling the turbidity of water during the draining process takes 11 minutes 13 seconds and when filling clean water takes 27 minutes 2 seconds. Ikan arwana membutuhkan kadar pH 6,8 – 7,5 dan tingkat kekeruhan 7,5 NTU. Pembuatan alat ini bertujuan untuk menjaga kadar pH dan kekeruhan air aquarium ikan arwana. Alat ini menggunakan sensor pH E-201-C untuk mengukur kadar pH, sensor turbidity SEM-0189 untuk mendeteksi kekeruhan air, sensor ultrasonik untuk mengukur ketinggian air dan menggunakan mikrokontroller ESP32. Pada pengontrolan kadar pH menggunakan metode fuzzy logic controller dengan mengunakan setpoint 7. Pada pengontrolan kadar pH menggunakan pompa mini up dan pompa mini down. Apabila kadar pH kurang dari 6,8 maka pompa mini up akan aktif begitu juga sebaliknya apabila kadar pH lebih besar dari 7,5 maka pompa mini down akan aktif. Sedangkan untuk pengontrolan kekeruhan air menggunakan pompa DC 12V 1 untuk membuang air kotor dan pompa DC 12V 2 untuk mengisi air bersih. Data yang terbaca oleh sensor dapat dipantau melalui OLED 128X64 dan aplikai blynk pada smartphone. Berdasarkan hasil pengujian pada sistem kendali kontrol kadar pH air aquarium ikan arwana dengan metode fuzzy dapat bekerja dengan memiliki nilai error kurang dari 0,4. Sedangkan pada pengontrolan kekeruhan air pada saat proses pengurasan membutuhkan waku 11 menit 13 detik dan pada saat pengisian air bersih membutuhkan waktu 27 menit 2 detik.